Distribution of Protozoan parasites in Drinking Water in Some Regions of Basra Province - Al-mounas, Mahmood S. Thamer (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study to identified and evaluate the prevalence of drinking water contamination with pathogenic protozoan parasites. A total of102 water samples were collect from three different sources of drinking water(34 plastic bottled , 32 samples house tank and 36 samples tap water , were collected from the house distributed by two regions, Al-Shamshomia and Al-Zubir ) in Basrah province, during the period of July to November 2018. Water samples were examined by direct method and by sedimentation and floatation methods. From 102 water samples45%in which Entamoeba histolytica is the most common parasites that were detected in39% water samples followed by Cryptosporidium sp.18% and then other types of algae and parasites but in lower rates.